Association Between Carbohydrate Quality Index During Pregnancy and Risk for Large-for-Gestational-Age Neonates: Results from the BORN 2020 Study - Antigoni Tranidou; Antonios Siargkas; Ioannis Tsakiridis; Emmanouela Magriplis; Aikaterini Apostolopoulou; Michail Chourdakis; Themistoklis Dagklis (Children)
Background/Objectives: To assess the association between early pregnancy carbohydrate quality, as measured by the Carbohydrate Quality Index (CQI), and the risk of delivering a large-for-gestational-age (LGA) infant in a Mediterranean pregnant cohort of northern Greece. Methods: We analyzed singleton pregnancies from the BORN 2020 prospective cohort in Greece. Dietary intake was assessed via a validated food frequency questionnaire, and CQI was computed from glycemic index, fiber density, whole-to-refined grain ratio, and solid-to-liquid carbohydrate ratio. Multivariable logistic regression was used to estimate the association between CQI (in tertiles) and LGA risk, defined as birthweight >90th percentile. Results: Among the 797 participants, 152 (19.1%) delivered LGA infants, and 117 (14.7%) were diagnosed with GDM. Of those with GDM, 23 (19.7%) delivered LGA infants. In the total population, higher maternal weight (p < 0.001), height (p = 0.006), and pre-pregnancy BMI (p = 0.004) were significantly associated with LGA. A greater proportion of women with LGA had a BMI > 25 (p = 0.007). In the GDM subgroup, maternal height remained significantly higher in those who delivered LGA infants (p = 0.017). In multivariable models, moderate CQI was consistently associated with increased odds of LGA across all models (Model 1: aOR = 1.60 (95% CI: 1.03–2.50), p = 0.037, Model 2: aOR = 1.57 (95% CI: 1.01–2.46), p = 0.046, Model 3: aOR = 1.58 (95% CI: 1.01–2.47), p = 0.044, Model 4 aOR: 1.70; 95% CI: 1.08–2.72; p = 0.023), whereas high CQI was not. In the GDM subgroup, a significant association between high CQI and increased LGA risk was observed in less adjusted models (Model 1 aOR: 6.74; 95% CI: 1.32–56.66; p = 0.039, Model 2 aOR: 6.64; 95% CI: 1.27–57.48; p = 0.044), but this was attenuated and became non-significant in the fully adjusted model (aOR: 3.05; 95% CI: 0.47–30.22; p = 0.28). When examining CQI components individually, no consistent associations were observed. Notably, a higher intake of low-quality carbohydrates (≥50% of energy intake) was significantly associated with increased LGA risk in the total population (aOR: 4.25; 95% CI: 1.53–11.67; p = 0.005). Conclusions: Higher early pregnancy intake of low-quality carbohydrates was associated with an elevated risk of LGA in the general population. However, CQI itself showed a non-linear and inconsistent relationship with LGA, with moderate, but not high, CQI linked to increased risk, particularly in GDM pregnancies, where associations were lost after adjustment. Both carbohydrate quality and quantity evaluations are essential, particularly in high-risk groups, to inform dietary guidance in pregnancy.